The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3168/jds.2009-2422
|View full text |Cite
|
Sign up to set email alerts
|

Mammary remodeling in primiparous and multiparous dairy goats during lactation

Abstract: Milk production is generally lower but lactation persistency higher in primiparous (PP) than in multiparous (MP) goats. This may be related to differences in development and maintenance of mammary gland function, but the underlying mechanisms are not well understood. The present study aimed to elucidate whether differences in lactational performance between PP and MP mammary glands are related to the time course of development and maintenance, not only of the mammary epithelial cell (MEC) population, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…Considering the period between early (day 10) and mid to late lactation (days 60–180), Safayi et al (2010) identified a reduction of alveoli proportion for both glands. In the case of lumen percentage, it stabilised (26–27%) and started to decrease in multiparous glands to its lowest level (20%) in late lactation.…”
Section: Mammary Gland Morphology During Lactation: Macroscopic and Mmentioning
confidence: 99%
“…Considering the period between early (day 10) and mid to late lactation (days 60–180), Safayi et al (2010) identified a reduction of alveoli proportion for both glands. In the case of lumen percentage, it stabilised (26–27%) and started to decrease in multiparous glands to its lowest level (20%) in late lactation.…”
Section: Mammary Gland Morphology During Lactation: Macroscopic and Mmentioning
confidence: 99%
“…The ability of the mammary gland to produce milk depends on number of epithelial cells which is influenced by their rate of proliferation and apoptosis (Knight, 2000; Capuco et al, 2003) and the secretory activity of the myoepithelial cells which is affected by their differentiation (Akers et al, 2006). The angiogenesis or vascular system development (Djonov et al, 2001) required for nutrient supply and removal of metabolic waste products has received no attention in normal mammary development of females (Akers, 2002) but was recently highlighted for goats (Safayi et al, 2010). Also, the metabolic status in the first lactating mammary gland is different because the nutrients are diverted between lactation and continued growth (Wathes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ramı´rez et al (1995a) observed a lower level of isolation in multiparous goats (8% of the goats were isolated in the last half hour before the birth, or not isolated), which may indicate greater calmness in multiparous goats, because the definition of isolation was similar to that of our study.The udder size of all goats (100%) in our study increased more than 5 cm at least 1 h before birth, which is in contrast to the study by Ramı´rez et al (1995a), who found that only 45% of all goats had increased udder size during the same hour. This may be due to differences in the physiology of primiparpus vs. muliparous mothers [development of the udder and maintenance of mammary gland function (Safayi et al 2010)]. This difference may also be explained by the fact that the mammary glands of multiparous goats may be more developed than those of the primiparous goats Time devoted to maternal care during the first hour after birth.…”
Section: Discussionmentioning
confidence: 99%